THE EFFECT OF LEADERSHIP AND ACHIEVEMENT MOTIVATION ON TEACHER PERFORMANCE AT STATE VOCATIONAL SCHOOL 2 PEKANBARU - Mulita, Yanti; Kartikowati, Rr Sri; Makhdalena (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2019)
This study aims at describing the effect of leadership and achievement motivation on teacher performance at SMK Negeri 2 Pekanbaru. The population in this study were all PNS (Civil Servant) teachers at SMKN 2 Pekanbaru. The total population was 107 people. The participants were obtained by using a simple random sampling technique to obtain a sample of 84 people. This qualitative descriptive research uses a type of correlative research. The data were obtained through questionnaire and documentation techniques. The collected data were then analyzed using descriptive analysis and path analysis. The results of the study showed that there was an influence of the principal's leadership on teacher performance. The coefficient of positive path analysis shows that there is a positive relationship between the principal's leadership and teacher's performance. It is found that the leadership of the school principal is very influential on teacher performance; there is a correlation between achievement motivation and teacher performance; and there is also a positive relationship between principal’s leadership and achievement motivation on teacher performance. Principal leadership influences teacher performance to increase work productivity in achieving goals.